Pengaruh Pembelajaran Fiqih dengan Multi Metode Terhadap Minat Belajar Siswa: (Studi Kasus di Madrasah Aliyah Umar Zahid Perak Jombang) - Adibah Adibah; Shofwatal Qolbiyyah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This study aims to determine the effect of learning Fiqh with multi methods on students' learning interest at Madrasah Aliyah Umar Zaid Perak Jombang. This research is a quantitative research, with a correlative approach. The data collection technique uses observation, interview, questionnaire and documentation methods, while the data analysis technique uses quantitative product moment analysis. The population of this study were all students at Madrasah Aliyah Umar Zahid Perak Jombang as many as 116 students, with a sample of 58 students. The results showed that learning Fiqh using multiple methods could influence students' learning interest with a correlation index (rxy) = 0.42. And these results can be interpreted at a significant level of 5% = 0.273 while at a level of 1% = 0.354. So it can be seen that rxy is greater than the significant level, then Ha is accepted and Ho is rejected. This means that there is a positive influence of learning Fiqh using multiple methods on the learning interest of Madrasah Aliyah Umar Zahid Perak Jombang students, with a correlation that is moderate or sufficient.